Association between unemployment, income, education level, population size and air pollution in Czech cities: evidence for environmental inequality? A pilot national scale analysis - Branis, Martin; Linhartova, Martina (Health & place, 2012)
We analyzed differentials in exposure to SO(2), PM(10) and NO(2) among Czech urban populations categorized according to education level, unemployment rate, population size and average annual salary. Altogether 39 cities were included in the analysis. The principal component analysis revealed two factors explaining 72.8% of the data variability. The first factor explaining 44.7% of the data variability included SO(2), PM(10), low education level and high unemployment, documenting that inhabitants with unfavorable socioeconomic status mainly reside in smaller cities with higher concentration levels of combustion-related air pollutants. The second factor explaining 28.1% of the data variability included NO(2), high salary, high education level and large population, suggesting that large cities with residents with higher socioeconomic status are exposed to higher levels of traffic-related air pollution. We conclude that, after more than a decade of free-market economy, the Czech Republic, a former Soviet satellite with a centrally planned economy, displays signs of a certain kind of environmental inequality, since environmental hazards are unevenly distributed among the Czech urban populations.
Keywords: společenská třída; monitorování životního prostředí; nezaměstnanost; Air Pollution; Cities; Retrospective Studies; Česká republika; Social Class; Unemployment; Environmental Monitoring; znečištění ovzduší; stupeň vzdělání; Czech Republic; městské obyvatelstvo; retrospektivní studie; Humans; Income; pilotní projekty; velkoměsta; příjem; Pilot Projects; Urban Population; Educational Status; lidé